Induced pluripotent stem cell for modeling Pompe disease - Huang, Wenjun; Zhang, Yanmin; Zhou, Rui (Frontiers in Cardiovascular Medicine, 2022)
Pompe disease (PD) is a rare, autosomal recessive, inherited, and progressive metabolic disorder caused by α-glucosidase defect in lysosomes, resulting in abnormal glycogen accumulation. Patients characteristically have multisystem pathological disorders, particularly hypertrophic cardiomyopathy, muscle weakness and hepatomegaly. Although the pathogenesis and clinical outcomes of PD is well-established, the disease modelling ability, mechanism elucidation, and drug development targeting PD have been substantially limited by the unavailable PD-relevant cell models. This obstacle has been overcome by the technology of induced pluripotent stem cell (iPSC) reprogramming, thus providing a powerful tool for cell replacement therapy, disease modelling, drug screening, and drug toxicity assessment. This review focused on the exciting achievement of PD disease modelling and mechanism exploration using iPSC.